P16 Methylation Is an Early Event in Cervical Carcinogenesis. Issue 3 (1st April 2011) - Huang, Lee-Wen; Pan, Hun-Shan; Lin, Yu-Hung; Seow, Kok-Min; Chen, Heng-Ju; Hwang, Jiann-Loung
Abstract : Background: Aberrant gene promoter methylation is a critical event in tumorigenesis. The aim of this study was to explore the promoter hypermethylation of p16 and DAPK1 during the progression of cervical precancerous lesions. Methods: A series of 98 cervical neoplasms (72 cervical intraepithelial neoplasia and 26 cervical carcinomas) were evaluated. The promoter methylation status of p16 and DAPK1 was assessed from cervical scrapings by methylation-specific polymerase chain reaction. Results: For p16, the frequency of promoter hypermethylation showed an increasing trend from normal to dysplastic to invasive squamous cancer specimens, and this increase reached statistical significance ( P < 0.0001). However, there was no significant difference in the promoter methylation state of DAPK1 with regard to the various grades of cervical lesions ( P = 0.077). Specifically, methylation of p16 was a frequent event in the cervical carcinoma samples, and these figures were statistically significant compared with the normal and cervical intraepithelial neoplasia I cases ( P = 0.015 and P = 0.021, respectively). Conclusions: These results imply that promoter hypermethylation of p16 occurs at an early stage of cervical neoplastic progression. This early event may play an initiating role in the malignant transformation of low-grade dysplasia into high-grade dysplasia and invasive carcinoma. We suggest that aberrant promoter methylation of p16 may serve as a useful biomarker during the follow-up of low-grade dysplasia.